PARLIAMENTARY THRESHOLD PADA PEMILIHAN UMUM LEGISLATIF TAHUN 2024 BERDASARKAN PERSPEKTIK TEORI KEDAULATAN RAKYAT - Nadilla Nur Farah; Mery Herlina; Dede Permana (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The parliamentary threshold is the minimum number of votes that a political party participating in an election must obtain in order to be included in the distribution of seats in the House of Representatives. Since its inception, the parliamentary threshold has always been a subject of debate because it is considered to be contrary to Article 1 paragraph (2) of the 1945 Constitution, which states that “sovereignty is in the hands of the people and is exercised in accordance with the law and the theory of popular sovereignty.” This study aims to determine the parliamentary threshold in the 2024 legislative elections based on the perspective of the theory of popular sovereignty and the impact of the parliamentary threshold on the 2024 legislative elections. The research method used is normative juridical with a legislative and conceptual approach. The results of this study indicate that the parliamentary threshold contradicts the values contained in Article 1 paragraph (2) and the theory of popular sovereignty, because both require power to come from the people, while the parliamentary threshold negates the voices of the people (voters) whose parties fail to reach the 4% parliamentary threshold requirement. The parliamentary threshold also has a huge impact on the representative system, consisting of positive impacts, namely simplifying the party system and improving the quality of people's representatives, as well as negative impacts, namely the waste of people's votes, political representation, and the dominance of political parties in parliament. Therefore, it is necessary to evaluate the parliamentary threshold regulation and also adjust it to the proportional election system with an open list.